Professional competences: intellectual structure of research - Guerrero Chanduví, Dante A. (2012)
This work aims to visualize the structure of research around professional competences through social network analysis of its research literature, taking into account the relationships among the authors who have written on the professional competences. The research sample includes publications in journals listed in the Web of Science database since 1950 to beginning of 2012. Maps made with the software Citespace II. The results obtained allow us to visualize the trends in the investigation of professional competences to present the conclusions.